Construction and optimization of human (Homo sapiens) mitochondrial DNA primers in the D-loop hypervariable segment II region in forensic biology - Nitisara , Antonia Anindyanari Paramartastri; Saamia, Vira; Purba, Laurentia Henrieta Permita Sari (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
DNA analysis is fundamental in forensic identification; however, nuclear DNA profiling often fails when samples are degraded. Mitochondrial DNA (mtDNA), which is maternally inherited and present in high copy numbers, provides a reliable alternative, particularly through analysis of the D-loop hypervariable segment II (HVS II). This study aimed to design and optimize human mtDNA HVS II–specific primers for forensic applications.An experimental approach combining in silico and in vitro methods was employed. Primer design and evaluation were conducted using the NCBI database, Primer3Plus, and NetPrimer Biosoft. Buccal swab samples from seven individuals were extracted using the PrepFiler™ Forensic DNA Extraction Kit, and DNA quality was assessed using a NanoVue spectrophotometer. Primer optimization was performed using gradient PCR, and sequencing was carried out using the Sanger method.Two primer pairs successfully amplified the HVS II region, generating fragments of 433–513 bp at an optimal annealing temperature of 56.5 °C. Sequence analysis revealed heteroplasmy and identified haplogroups N21 and L4b within the same maternal lineage. Both in silico and in vitro results confirmed that the designed primers specifically and reliably amplified human mtDNA.In conclusion, the optimized HVS II primers demonstrate strong potential for forensic casework involving degraded or limited biological samples and support improved resolution in population-level mtDNA analyses.